Assessing combined effects of varenicline and N‐acetylcysteine on reducing nicotine seeking in rats. (22nd February 2022) - Nall, Rusty W.; Beloate, Lauren N.; Meyerink, Michael E.; Penaloza, Tiffany; Doolittle, Jade; Froeliger, Brett; Kalivas, Peter W.; Garcia‐Keller, Constanza
Abstract: Nicotine addiction is a chronic relapsing brain disorder, and cigarette smoking is the leading cause of preventable death in the United States. Currently, the most effective pharmacotherapy for smoking cessation is Varenicline (VRN), which reduces both positive and negative reinforcement by nicotine. Clinically, VRN attenuates withdrawal symptoms and promotes abstinence, but >50% of smokers relapse within 3 months following a quit attempt. This may indicate that VRN fails to ameliorate components of nicotine‐induced neuroplasticity that promote relapse vulnerability. Animal models reveal that glutamate dysregulation in the nucleus accumbens is associated with nicotine relapse. N‐acetylcysteine (NAC) normalizes glutamate transmission and prolongs cocaine abstinence. Thus, combining VRN and NAC may promote and maintain, respectively, nicotine abstinence. In rats, we found that VRN effectively reduced nicotine self‐administration and seeking in early abstinence, but not seeking later in abstinence. In contrast, NAC reduced seeking only later in abstinence. Because VRN and NAC are sometimes associated with mild adverse effects, we also evaluated a sequential approach combining subthreshold doses of VRN during self‐administration and early abstinence with subthreshold doses of NAC during late abstinence. As expected, subthreshold VRN did not reduce nicotine intake. However, subthreshold VRN and NAC reduced seeking in late abstinence, suggesting a combined effect. Overall, our results suggest that combining subthreshold VRN and NAC is a viable and drug‐specific approach to promote abstinence and reduce relapse while minimizing adverse effects. Our data also suggest that different components and time points in addiction engage the different neurocircuits targeted by VRN and NAC. Abstract : Using a translational rat model (A and C), we assessed whether a pharmacological therapy sequentially combining varenicline (VRN) and N‐acetylcysteine (NAC) could reduce nicotine intake and relapse. We found that the full dose VAR reduced nicotine intake and the full dose of NAC reduced nicotine seeking. Furthermore, subthreshold dose of VRN during nicotine intake and subthreshold dose of NAC during abstinence prevented cue‐induced reinstatement (B). Thus, our results suggest that sequentially combining VAR and NAC subthreshold doses, likely through action in distinct neurocircuits targeted by each drug, can reduce smoking and relapse while minimizing adverse effects in humans.